2020
DOI: 10.1016/j.jsxm.2020.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Motivation and Satisfaction Among Consensually Non-Monogamous and Monogamous Individuals

Abstract: Background Previous research has found differences in sexual motives and, separately, sexual satisfaction in consensually non-monogamous (CNM) and monogamous individuals and that these constructs are related to relationship outcomes (eg, relationship quality). Aims The present study sought to refine and expand on previous research by (i) using a more common, validated measure of sexual motives, (ii) measuring sexual satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…This may be explained by the nature of the consensual agreement itself. Arguably, CNM individuals may seek other partners and alternative sexual experiences to explore their own sexual needs without damaging the primary relationship, but at the same time actively work on the sexual aspects of their primary relationship to feel emotionally connected to their primary partner and avoid any feeling that they are becoming less important in their lives (Mogilski et al, 2017;Moors et al, 2017;Rodrigues et al, 2017Rodrigues et al, , 2019Wood et al, 2018;Mitchell et al, 2020). Findings for this group of individuals clearly show the importance of accounting for relationship agreements and the use of pornography with the primary partner, rather than pornography use in itself, when examining relationship outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This may be explained by the nature of the consensual agreement itself. Arguably, CNM individuals may seek other partners and alternative sexual experiences to explore their own sexual needs without damaging the primary relationship, but at the same time actively work on the sexual aspects of their primary relationship to feel emotionally connected to their primary partner and avoid any feeling that they are becoming less important in their lives (Mogilski et al, 2017;Moors et al, 2017;Rodrigues et al, 2017Rodrigues et al, , 2019Wood et al, 2018;Mitchell et al, 2020). Findings for this group of individuals clearly show the importance of accounting for relationship agreements and the use of pornography with the primary partner, rather than pornography use in itself, when examining relationship outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that the relational experiences of monogamous individuals do not differ from those of CNM individuals (e.g., Rubel & Bogaert, 2015). For example, both groups of individuals report similar levels of sexual satisfaction with their primary partner (Conley et al, 2018;Mitchell et al, 2020) and tend to activate similar relationship protective strategies with their primary partner (Mogilski et al, 2017). Despite this lack of differences in relationship quality, CNM individuals tend to report more sex-related intrinsic motives for having sex (e.g., sexual activity enjoyment, sex drive satisfaction; Wood et al, 2018; but see Mitchell et al, 2020) and more nonsexual benefits (e.g., need fulfilment; Moors et al, 2017) than their monogamous counterparts.…”
Section: Relationship Agreements and Relationship Qualitymentioning
confidence: 99%
See 3 more Smart Citations